Grensesnittets estetikk: En begrepsanalytisk tilnærming til samtidsestetikken og dens medieparadigme - Malvik, Anders Skare (Tidskrift för litteraturvetenskap, 2009)
The Aesthetics of the Interface In this article I suggest deploying the word interface as a critical concept for probing the complex relations between contemporary art and literature and so-called media culture. An interface designates a surface forming a common boundary between two bodies, spaces or phases. It also designates the place where independent and often unrelated systems meet and act on or communicate with each other. In computer culture, the interface is commonly understood as the means by which humans interact with computers, be it the screen, the mouse-pad, the operative systems, and the endless list of software programs that we interact with on a daily basis. With the arrival of the network computer, the computer interface also becomes a means of human interaction and communication – a technological device for cultural interfacing. Inspired by Mieke Bals method of concept analysis I suggest making interface an analytical concept. I do this by analyzing two short texts by the Norwegian author and visual artist Matias Faldbakken. I distribute the concept of interface along the strands of making, storing and transmitting. Confronting the short texts with the concept of interface under these headings allows us to suggest connections between the meaning of interface as production technology, as a site for discursive and historical convergence in the aesthetical object, and finally as the crucial interconnection between reader/viewer and text/artpiece. The article outlines an itinerary of an »aesthetic of the interface« through which the concepts of convergence, repetition and transgression become important concepts of Faldbakken’s aesthetics that connects to and works with its relation to present day media culture.